Analysis of XRD Characterization of Fe3O4/Polypyrrole Nanocomposite Prepared by Sol-Gel Method - Febriani, Annisa; Ramli, -; Gusnedi, -; Darvina, Yenni (Department of Physics – Universitas Negeri Padang UNP, 2024)
Nanocomposites can be thought of as solid structures with nanometer-scale dimensions that repeat at the distances between different structural constituents. In this study, Fe3O4 was used as a filler and Polypyrrole polymer as the matrix material. This research was conducted by varying the Fe3O4: Polypyrrole composition of 5 variations including 30%, 40%, 50%, 60%, and 70% w/w. This research was conducted to analyze the results of the XRD characterization of Fe3O4/Polypyrrole nanocomposite using the sol-gel method. The tool used in this research is X-Ray Diffraction (XRD) obtained the phase structure, crystal size, and microstrain. Based on the results of the study, the greater the polypyrrole composition, the greater the crystal size and microstrain. Details of the results are described in this paper.